Execute of Chemotherapy Medicines on Cancer Patients - Vaidya, Sunita N. (Asian Journal of Pharmaceutics (AJP), 2023)
Chemotherapy still has several side effects that might lower a patient’s quality of life, despite improvements in chemotherapeutic techniques and drugs. This review’s objective is to identify and characterize the adverse effects that are unique to chemotherapy. This essay provides a thorough analysis of the major side effects that have an impact on chemotherapy patients’ overall health. Cancer patients also encounter a wide range of symptoms, both physical and psychological. These symptoms can be a result of the sickness or the medication and can vary in frequency, severity, and level of distress.